Of neoliberalism and global health: human capital, market failure and sin/social taxes. Issue 5 (19th October 2016) - Reubi, David
Abstract: This article tells a different but equally important story about neoliberalism and global health than the narrative on structural adjustment policies usually found in the literature. Rather than focus on macroeconomic structural adjustment policies, this story draws our attention to microeconomic taxation policies on tobacco, alcohol and sugar now widely recognised as the best strategy to control the global non-communicable disease epidemic. Structural adjustment policies are the product of the shift from statist to market-based development models, which was brought about by neoliberal thinkers like Peter Blau and Deepak Lal. In contrast, taxation policies are the result of a different epistemological rupture in international development: the move from economies and physical capital to people and human capital, advocated by Gary Becker and others. This move was part of wider change, which saw Chicago School economists, under the influence of rational choice theory, redefine the object of their discipline, from the study of markets to individual choices. It was this concern with people and their choices that made it possible for Becker and others to identify the importance of price for the demand for tobacco, alcohol and sugar. The same concern also made it easier for them to recognise that there were inefficiencies in the tobacco, alcohol and sugar markets that required government intervention. This story, I suggest, shows that structural adjustment policies and pro-market ideology do not exhaust the relationship between neoliberalism and global health and should not monopolise how we, as political and social scientists, conceive it.